2023
DOI: 10.3390/membranes13050464
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral Surfaces in the Fight against the Spread of Coronaviruses

Abstract: This review is conducted against the background of nanotechnology, which provides us with a chance to effectively combat the spread of coronaviruses, and which primarily concerns polyelectrolytes and their usability for obtaining protective function against viruses and as carriers for anti-viral agents, vaccine adjuvants, and, in particular, direct anti-viral activity. This review covers nanomembranes in the form of nano-coatings or nanoparticles built of natural or synthetic polyelectrolytes––either alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 183 publications
(233 reference statements)
0
2
0
Order By: Relevance
“…After the initial two intramuscular doses of thirty micrograms of BNT162b2 mRNA, the antibody titers start to decline a few months after the final immunization; hence, a booster dose is required. Research has demonstrated that chitosan and its derivatives possess potential anti-SARS-CoV-2 action, operate as useful adjuvants in vaccines, and exhibit direct antiviral activity [ 111 ]. For instance, plasmid DNA encoding the nucleocapsid SARS-CoV-2 was delivered intranasally using chitosan nanoparticles as a stimulant.…”
Section: Nanovaccinesmentioning
confidence: 99%
“…After the initial two intramuscular doses of thirty micrograms of BNT162b2 mRNA, the antibody titers start to decline a few months after the final immunization; hence, a booster dose is required. Research has demonstrated that chitosan and its derivatives possess potential anti-SARS-CoV-2 action, operate as useful adjuvants in vaccines, and exhibit direct antiviral activity [ 111 ]. For instance, plasmid DNA encoding the nucleocapsid SARS-CoV-2 was delivered intranasally using chitosan nanoparticles as a stimulant.…”
Section: Nanovaccinesmentioning
confidence: 99%
“…Designing new synthetic peptides can be used not only to enhance their antimicrobial effects but also for broader applications in various fields [ 21 ]. With the proper design and selection of amino acid sequences, synthetic peptides can be integrated into the surface matrix or the material of the product itself, thereby providing long-lasting protection against microbes [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%